On the Scientific and Philosophical Implications of the Missing Mass Problem - Pabjan, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
The article deals with the so called missing mass problem which during the last three decades has become one of the most serious difficulties in physics. There is some strong empirical evidence that the Universe contains not only matter that can be seen (by telescopes or radio telescopes) but the huge quantities of the unseen matter as well. The ordinary matter known to physics is but a small part of all matter the Universe is composed of. The missing mass is supposed to be in the form of the dark matter and the dark energy. In the paper the arguments in favor of the existence of these two entities are outlined, and some scientific as well as philosophical implications of the missing mass problem are discussed. It is argued that all the proposed solutions of this problem lead to serious changes in the scientific and philosophical worldview.